1995
DOI: 10.1002/ajmg.1320550125
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor gene (CAG)n repeat analysis in the differential diagnosis between Kennedy disease and other motoneuron disorders

Abstract: An increase in the number of (CAG)n repeats in the first coding exon of the androgen receptor (AR) gene has been strongly associated with Kennedy disease (KD) (spinal and bulbar muscular atrophy). This is an X-linked hereditary disorder characterized by motoneuron degeneration occurring in adults together with gynecomastia and hyperestrogenemia. We have performed AR gene molecular analysis in several members of a large family with KD as well as in 25 sporadic patients suffering from heterogeneous motoneuron di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…Despite this dominant toxic property, women rarely show symptoms of the disease, although some mild cases have been reported (Ferlini et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this dominant toxic property, women rarely show symptoms of the disease, although some mild cases have been reported (Ferlini et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Esses achados indicam que a análise por PCR do gene do receptor androgênico dos trinucleotídeos repetidos desempenha um papel preciso no diagnóstico diferencial entre doença de Kennedy e outras síndromes clinicamente similares neste grupo heterogêneo de doenças neurológicas 16,17 . Do ponto de vista clínico, nossos três pacientes são típicos de doença de Kennedy.…”
Section: Discussionunclassified
“…In our experience, the diagnosis of SBMA was suspected in several patients but was then ruled out by molecular analysis showing normal CAG number. Recently, Jobsis et al [20] and Ferlini et al [21] showed the role now played by the analysis of (CAG)n repeats of the AR gene in the differential diagnosis of Kennedy's dis ease among motoneuron diseases.…”
Section: Discussionmentioning
confidence: 99%